2007
DOI: 10.1016/j.crte.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Processus et bilan des flux hydriques d’un bassin versant de milieu tropical de socle au Bénin (Donga, haut Ouémé)

Abstract: Avis : Ce texte est la version de l'auteur d'une oeuvre acceptée en vue de sa publication dans les Comptes-Rendus Geoscience. Il est dès lors possible que les modifications résultant du processus de publication, et notamment de l'examen par les pairs, la révision, l'édition, les corrections, la mise en page structurelle et les autres dispositifs de contrôle de qualité ne soient pas reprises dans le présent document. Il est possible que des modifications aient été apportées à la présente oeuvre après qu'elle ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
(24 reference statements)
1
17
1
Order By: Relevance
“…This study proposes that the permanent water table may actually contribute to base flow in this environment, which has not been considered before, on the basis of hydrological and geochemical data [Kamagat e et al, 2007;S eguis et al, 2011b]. However, only the upper section of the water table, located within a higher permeability unit is contributing to base flow, similarly to interflow processes.…”
Section: Discussion On the Conceptual Modelmentioning
confidence: 93%
See 4 more Smart Citations
“…This study proposes that the permanent water table may actually contribute to base flow in this environment, which has not been considered before, on the basis of hydrological and geochemical data [Kamagat e et al, 2007;S eguis et al, 2011b]. However, only the upper section of the water table, located within a higher permeability unit is contributing to base flow, similarly to interflow processes.…”
Section: Discussion On the Conceptual Modelmentioning
confidence: 93%
“…The water table below the Ara River may or may not reach the riverbed. At larger scales (13, 105, and 586 km 2 ) including the study area, previous studies using geochemistry have shown that the contribution of permanent groundwater (identified by high water mineralization) to streamflow is negligible and that permanent groundwaters are disconnected from the streams [Kamagat e et al, 2007;S eguis et al, 2011b]. Field observations show that a perched water table within the hardpan exfiltrates water above the river bed, across the slope break in the downstream section.…”
Section: 1002/2014wr015773mentioning
confidence: 96%
See 3 more Smart Citations